Analisis Semiotika Unsur-Unsur Kebudayaan Batak Pada Film Ngeri-Ngeri Sedap - Seftiani, Wiranti; Murdiati, Eni; Jawasi, Jawasi (Social Science and Contemporary Issues Journal, 2024)
A movie is an audio-visual communication tool used by its maker to convey a message. Given the diverse ethnicities and tribes in Indonesia, movies should provide fair information about culture. The movie Ngeri-Ngeri Sedap was released in mid-2022. The drama genre film written by Bene Dion Rajagukguk focuses on a Toba Batak family conflict. The Batak culture that appears very complex makes this movie very debatable. The Toba Batak culture depicted in the movie Ngeri-Ngeri Sedap is the subject of this research. This research uses Roland Barthes' theory of denotation, connotation and myth. This research method uses a descriptive qualitative approach. Primary data of this research is Ngeri-Ngeri Sedap movie and secondary data is obtained from books, journals and the internet. The data collection techniques used in this research are observation and documentation. The results of the research and discussion show that the Ngeri-Ngeri Sedap movie is proven to have elements of Batak culture, as well as the denotation meaning contained in the film, namely food, customs and language, connotation makes the real meaning, and the myth in this movie is the legend of Lake Toba, and Holbung Hill.